Qualitative analysis of mothers' perception related to the delivery of information regarding preterm births - Doriane Randriamboarison; Elisa Fustec; Isabelle Enderlé; Mathilde Yverneau; Karine Le Breton; Linda Lassel; Nadia Mazille-Orfanos; Patrick Pladys (BMC, 2024)
Abstract Background Preterm birth is a major health issue due to its potential outcomes and socioeconomic impact. Prenatal counseling is of major importance for parents because it is believed that the risk of preterm birth is associated with a higher parental mental burden. Nowadays in France, the content and delivery of antenatal counseling is based on personal experience since there is a lack of official guidelines. The goal of the study was to evaluate maternal perception of antenatal information delivered in the setting of preterm births. Methods A qualitative study was performed using semi-structured individual interviews of 15 mothers with a child born > 26-34 GW. Data analysis was based on a constant comparative method. Results Concerning prenatal counseling content, parents wanted to be informed of their role in the care of their preterm child more so than statistics that were not always considered relevant. Parents' reactions to the announcement of the risk of a preterm birth was dominated by stupefaction, uncertainty and anxiety. When it comes to the setting of prenatal counseling, patients' room was deemed an appropriate setting by parents and ideally the presence of a coparent was appreciated as it increased patients' understanding. The physicians' attitude during the counseling was considered appropriate and described as empathic and optimistic. The importance of support throughout the hospitalization in the form of other parents' experiences, healthcare professionals and the possibility to preemptively visit the NICU was emphasized by participants. Delivery experience was dominated by a sense of uncertainty, and urgency. Some leads for improvement included additional support of information such as virtual NICU visit; participants also insisted on continuity of care and the multidisciplinary aspect of counseling (obstetrician, neonatologist, midwife, nurse, lactation consultant and psychologist). Conclusion Highlighting parents' expectations about prenatal counseling could lead to the establishment of overall general guidelines. However, some topics like the use of statistics and mentioning the risk of death underline the importance of a personalized information.